The Peach and the Sky - WEE, TZE (NGĀ-TAI) (Te Kaharoa, 2019)
Tao laid in bed staring at an old black and white photo of his mother; twirling a little peach-shaped jade pendant between his fingers; a gift given to him by his mother. Tao’s name meant peach in Chinese, he was given the name by his mother; as a baby, he was a chubby and sweet little thing, now, a young 17-year-old man; slim, gaunt and bitter. Tao closed his eyes trying to remember the sweet, fragrant aroma of orange blossoms whenever his mother walked into the room, how gently she spoke, even when angered, her hands; soft and warm against his cheeks as she placed a tender kiss on his forehead. Tao thought of these memories religiously every morning, it made him feel closer to his mother even though they were oceans apart.